2005
DOI: 10.1007/s00402-005-0814-6
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic hemipelvectomy: case report and literature review

Abstract: Traumatic hemipelvectomy is a rare but devastating injury involving complete disruption of the hemipelvis from the pubic symphysis to the sacroiliac joints and often results in death. We present an interesting case of traumatic hemipelvectomy caused by a previously undescribed mechanism of injury in which judicious angiography and aggressive surgical treatment contributed to patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 15 publications
0
52
1
1
Order By: Relevance
“…This leaves the limb functionally and anatomically useless. Despite this, it has been reported that in more than 50% of cases, the limb is still attached to the patient by a bridge of skin following this injury [2,13]. This was demonstrated in this case.…”
Section: Mechanism Of Injurycontrasting
confidence: 42%
See 3 more Smart Citations
“…This leaves the limb functionally and anatomically useless. Despite this, it has been reported that in more than 50% of cases, the limb is still attached to the patient by a bridge of skin following this injury [2,13]. This was demonstrated in this case.…”
Section: Mechanism Of Injurycontrasting
confidence: 42%
“…This is particularly true in the rural areas which are also devoid of health care facilities equipped to handle adequate resuscitation of victims of major trauma. More often than not, advanced resuscitation techniques including arterial embolization and emergency operative exploration are necessary to achieve haemostasis [2]. Our patient sustained this injury in a rural environment and received initial management at a primary health care facility where she received sub-optimal care by the standards of her injuries.…”
Section: Reasons For Delay and Peculiarities Of Management In Our Envmentioning
confidence: 92%
See 2 more Smart Citations
“…The survivors, almost < 30 years, were healthy individuals able to tolerate massive hemorrhage and soft-tissue destruction [16,22,23]. Patients with complete hemipelvectomy seem to have a better chance of survival than patients with partial hemipelvectomy.…”
Section: Discussionmentioning
confidence: 99%